Leadership Development Program: The Correlation Between Training Design and Training Transfer Based On the Islamic Perspective - Mohd Zainol, Noor Azmi; Mohamed, Hasan Al-Banna (Universiti Utara Malaysia Press, 2024)
Training management literature highlighted that the leadership development training design consists of two important features: training content and training method. The ability of the management to appropriately implement such program features may lead to enhanced training transfer in the organizations. Reviews of the literature on leadership development found that the literature is mostly dominated by Western scholar perspectives. Although this relationship has been studied in the Islamic management views, the leadership development training design only contributed little explanation of workplace training programs. Most Islamic scholars in this field of study only discussed conceptually without suggesting a framework that can serve as a guide for the subsequent measurement. Therefore, this study was undertaken to determine the relationship between leadership development training design and training transfer using questionnaires with 412 leaders in the Malaysian Army Infantry Corps. The path model of SmartPLS version 3.2.5 results stated that there is a significant relationship between the training content and training transfer, and there is a significant relationship between the training method and training transfer. These outcomes showed two important findings. Firstly, the relationship between training content significantly correlated with training transfer. Secondly, the relationship between training methods significantly correlated with training transfer. Statistically, this result demonstrates that the leadership development training design acts as an important antecedent of training transfer in organizations. Further, the discussions, implications and conclusion are elaborated.